2021
DOI: 10.3390/medicines8090047
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of the Efficacy of Systemic Enzymes and Probiotics in the Resolution of Post-COVID Fatigue

Abstract: Muscle fatigue and cognitive disturbances persist in patients after recovery from acute COVID-19 disease. However, there are no specific treatments for post-COVID fatigue. Objective: To evaluate the efficacy and safety of the health supplements ImmunoSEB (systemic enzyme complex) and ProbioSEB CSC3 (probiotic complex) in patients suffering from COVID-19 induced fatigue. A randomized, multicentric, double blind, placebo-controlled trial was conducted in 200 patients with a complaint of post-COVID fatigue. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 54 publications
0
51
1
2
Order By: Relevance
“…Results of a randomized controlled trial involving 200 patients with COVID-19 showed that a 14-day probiotic supplementation of Bacillus coagulans , Bacillus subtilis and Bacillus clausii combined with systemic enzymes with immunomodulatory potential (serratiopeptidase, bromelain, amylase, lysozyme, peptidase, catalase, papain, glucoamylase and lactoferrin) improved physical and mental fatigue in individuals recovered from COVID-19 (ref. 177 ). Another randomized controlled trial of 300 participants also found that supplementation of a probiotic formula consisting of Lactiplantibacillus plantarum and Pediococcus acidilactici in patients with COVID-19 was associated with a reduction in nasopharyngeal viral load, lung infiltrates, shortened duration of clinical symptoms by 2–7 days and improved immune response in the intervention group compared with the control group receiving placebo 178 .…”
Section: Microbiota-based Interventionsmentioning
confidence: 99%
“…Results of a randomized controlled trial involving 200 patients with COVID-19 showed that a 14-day probiotic supplementation of Bacillus coagulans , Bacillus subtilis and Bacillus clausii combined with systemic enzymes with immunomodulatory potential (serratiopeptidase, bromelain, amylase, lysozyme, peptidase, catalase, papain, glucoamylase and lactoferrin) improved physical and mental fatigue in individuals recovered from COVID-19 (ref. 177 ). Another randomized controlled trial of 300 participants also found that supplementation of a probiotic formula consisting of Lactiplantibacillus plantarum and Pediococcus acidilactici in patients with COVID-19 was associated with a reduction in nasopharyngeal viral load, lung infiltrates, shortened duration of clinical symptoms by 2–7 days and improved immune response in the intervention group compared with the control group receiving placebo 178 .…”
Section: Microbiota-based Interventionsmentioning
confidence: 99%
“…Lumbrokinases are another orally active [ 960 ] set of fibrinolytic enzymes that have been found in earthworms [ 961–965 ], and may also be produced recombinantly [ 966 , 967 ]; they may also have some tPA activity [ 965 ]. Each has been proposed as of value in acute and/or Long COVID treatment [ 751 , 958 , 968 ]. With two (positive) exceptions [ 968 , 969 ], and another planned [ 970 ], randomised controlled trials are awaited.…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…Each has been proposed as of value in acute and/or Long COVID treatment [ 751 , 958 , 968 ]. With two (positive) exceptions [ 968 , 969 ], and another planned [ 970 ], randomised controlled trials are awaited. In the plant kingdom, bromelain (from pineapples) is a cysteine protease found in pineapple tissue [ 971–974 ].…”
Section: Anticoagulants Platelet Inhibitors and The Triple Treatmentmentioning
confidence: 99%
“…[47][48][49] ImmunoSEB and ProbioSEB CSC3 were shown in combination in a randomized controlled trial to have benefit in treating fatigue symptoms (91% resolution of fatigue vs. 15% in treatment vs. placebo groups after 14 days). 47 ImmunoSEB is a multienzyme formulation, which contains enzymes such as bromelain and papain, and Pro-bioSEB CSC3 contains various strains of Bacillus probiotics. Similarly, Apportal, which is a nutritional supplement that contains various vitamins, minerals, amino acids, and plant extracts, and Pycnogenol, an extract from French Maritime pine bark, were shown separately in 2 prospective, open-label studies to have benefit in treating fatigue symptoms after short treatment courses of a few weeks to a month.…”
Section: Scoping Reviewmentioning
confidence: 99%